Professionally Important Qualities of Bachelors in Technosphere Safety - Алексей В. Ермилов; Лев В. Мардахаев; Ольга И. Воленко (Rossijskij psihologičeskij žurnal., 2020)
Introduction. Professional development of cadets training under the Technosphere Safety program, 03.20.01 (hereinafter, referred to as bachelors) is largely characterized by the development of professionally important qualities. Professionally important qualities of bachelors are shaped at the university. Educationalists’ understanding of such qualities enables them to find the ways to improve the quality of vocational training. To date, this is the first study to distribute professionally important qualities into groups depending on bachelors’ operational actions in risk situations. Methods. These were questioning and analysis of psychological, pedagogical, and specialized literature. The study used the personality-activity approach to analyze and interpret professionally important qualities. The sample comprised of 71 mid-level and high-level commanding officers of the Ministry for Extraordinary Situations of Russia. At the first stage the authors specified 23 professional qualities that are important for bachelors and also four groups of their manifestation. At the second stage, the questionnaire-based data enabled authors to distribute qualities into groups. Each group contained the most important quality. Results. This section describes the distinguished groups of professionally important qualities , including (a) universal qualities (courage), (b) qualities important for professional activities (speed of assessment of operational situations), (c) qualities providing staff management (leadership), and (d) qualities of self-management (stress tolerance). Discussion. The authors consider professionally important qualities as a component of bachelors’ success in environments with risk factors. The findings of the study are of particular interest to universities. The studied qualities may be used to evaluate graduates’ personality and to determine failures in their training. This aspect enables educationalists to purposefully create special conditions for the manifestation of professionally important qualities of a certain group in the educational process.